2016
DOI: 10.1097/ta.0000000000001078
|View full text |Cite
|
Sign up to set email alerts
|

Shorter times to packed red blood cell transfusion are associated with decreased risk of death in traumatically injured patients

Abstract: Therapeutic/care management study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 14 publications
2
62
0
2
Order By: Relevance
“…Additionally, the median transport duration in our study was 35 min, and the administration of RCCs to patients in the field therefore facilitated earlier access to RCCs than in‐hospital administration. Early administration of packed red blood cells was recently associated with reduced odds of mortality in a North American trauma system . Every 10 min delay in administration of packed red blood cells was associated with a 27% increase in the odds of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the median transport duration in our study was 35 min, and the administration of RCCs to patients in the field therefore facilitated earlier access to RCCs than in‐hospital administration. Early administration of packed red blood cells was recently associated with reduced odds of mortality in a North American trauma system . Every 10 min delay in administration of packed red blood cells was associated with a 27% increase in the odds of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Early administration of packed red blood cells was recently associated with reduced odds of mortality in a North American trauma system. 3 Every 10 min delay in administration of packed red blood cells was associated with a 27% increase in the odds of mortality. We are unable to confirm these findings as our study does not compare mortality rates after introduction of the RCC guideline with those prior to its implementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, several retrospective studies have found that early administration of RBCs led to decreased mortality in severely injured patients (3436). One study also demonstrated a decreased frequency of TIC in blunt trauma patients who received prehospital RBCsas compared to standard resuscitation methods (36), and the practice of providing prehospital blood, especially in air ambulances, appears to be growing.…”
Section: Prehospital Settingmentioning
confidence: 99%